Sheepfolds induce significant increase of seasonal CO2, CH4 and N2O emissions in temperate steppes of Inner Mongolia - Wang, Xinyu; Guo, Xudong; Zhou, Di; Wang, Hao; Li, Haoxin; Li, Frank Yonghong (Frontiers in Ecology and Evolution, 2023)
The changes in grassland management and grassland types are strongly linked with dynamics in soil physico-chemical properties and vegetation attributes, with important implications for carbon/nitrogen cycling and greenhouse gas (GHG) fluxes. However, the seasonal variations of GHG emissions from sheepfolds, and the underlying biotic and abiotic drivers affecting GHG exchanges across different steppe and management types remain largely unclear. Taking the Inner Mongolian grassland as a model system, we measured the fluxes of CO2, CH4 and N2O, as well as soil and vegetation variables, in three contrasting grassland management areas (grazing, sheepfold, enclosure) and in three representative (wet typical, dry typical, desert) grassland ecosystems in July, September and November 2016. Our results showed that: (1) GHG fluxes were mostly higher in the plant growing season (July and September) than in the non-growing season (November); sheepfold area had significantly higher GHG emissions (in July and mean over the season) than enclosed and grazing areas, with the effects being most pronounced in dry typical steppe. (2) The high GHG emissions in dry typical steppe were closely associated with the interactions among favorable soil temperature and moisture, high total organic carbon (TOC) content, and high aboveground biomass. The important predictors for CO2 emission were soil TOC and pH, whereas that for CH4 and N2O emissions were soil temperature and moisture content, in sheepfold areas. (3) Three GHG emissions were negatively affected by species richness across all steppe and management types, which might be a consequence of indirect effects through the changes in soil TOC and total nitrogen (TN). These results indicate that sheepfold areas are intensive hotspot sources of GHGs in the steppes, and it is of great importance to help to account GHG emissions and develop mitigation strategies for sheepfold areas for sustainable grassland management in the natural steppe based pastoral production ecosystems.